2000
DOI: 10.1089/088922200308738
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Distribution and Coding Capacity of the Human Endogenous Retrovirus HERV-W Family

Abstract: Some genomic elements of the multicopy HERV-W endogenous retroviral family have been previously identified in databases. One of them, located on chromosome 7, contains a single complete open reading frame (ORF) putatively encoding an envelope protein. We have experimentally investigated the genomic complexity and coding capacity of the HERV-W family. The human haploid genome contains at least 70, 100, and 30 HERV-W-related gag, pro, and env regions, respectively, widely and heterogeneously dispersed among chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
2
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 42 publications
5
68
2
5
Order By: Relevance
“…On the other hand, retroviral copies are under-represented on smaller chromosomes 16, 17, 19, 20, and 22. Generally, HERV-W elements show biased distribution toward chromosomes 3, 4, X, and particularly Y, and are less frequent on chromosomes 16, 17, 20, and 22, in agreement with experimental results (Voisset et al 2000).…”
Section: Genomic Distributionsupporting
confidence: 90%
“…On the other hand, retroviral copies are under-represented on smaller chromosomes 16, 17, 19, 20, and 22. Generally, HERV-W elements show biased distribution toward chromosomes 3, 4, X, and particularly Y, and are less frequent on chromosomes 16, 17, 20, and 22, in agreement with experimental results (Voisset et al 2000).…”
Section: Genomic Distributionsupporting
confidence: 90%
“…The number of identified HERV-W related fragments, at least 70 copies for gag , 30 copies for env per haploid genome, is correlated with the increase in complexity from env to gag and pro regions previously described (Voisset et al ., 2000). We previously isolated fifteen env and twenty-four pol members of the HERV-W family using human monochromosomal DNAs and suggested that ret-rotransposition or chromosomal translocation had occurred during hominid evolution (Kim and Lee, 2001;Kim, 2001).…”
Section: Resultsmentioning
confidence: 52%
“…Parmi les différents HERV, le sous-type W (HERV-W) semble particulièrement impliqué en psychiatrie. Au moins 140 séquences appartenant à la famille HERV-W ont pu être identifiées dans l'ADN humain à ce jour dont seulement 40 présentent une séquence complète [13]. Le HERV-W a une distribution chromosomique ubiquitaire à l'exception, actuellement connue, des chromosomes 16 et 22 [12].…”
Section: Les Herv Dans La Schizophrénie Et Le Trouble Bipolaireunclassified